Quantitative estimation of enzymatic released specific oligosaccharides from Hericium erinaceus polysaccharides using CE-LIF - Yong Deng; Jing Zhao; Shaoping Li (Journal of Pharmaceutical Analysis, 2023)
Polysaccharides exhibit multiple pharmacological activities which are closely related to their structural features. Therefore, quantitatively quality control of polysaccharides based on their chemical characteristics is important for their application in biomedical and functional food sciences. However, polysaccharides are mixed macromolecular compounds that are difficult to isolate and lack standards, making them challenging to quantify directly. In this study, we proposed an improved saccharide mapping method based on the release of specific oligosaccharides for the assessment of Hericium erinaceus polysaccharides from laboratory cultured and different regions of China. Briefly, a polysaccharide from H. erinaceus was digested by β-(1-3)-glucanase, and the released specific oligosaccharides were labeled with 8-aminopyrene-1,3,6-trisulfonic-acid (APTS) and separated by using micellar electrokinetic chromatography (MEKC) coupled with laser induced fluorescence (LIF), and quantitatively estimated. MEKC presented higher resolution compared to polysaccharide analysis using carbohydrate gel electrophoresis (PACE), and provided great peak capacity between oligosaccharides with polymerization degree of 2 (DP2) and polymerization degree of 6 (DP6) in a dextran ladder separation. The results of high performance size exclusion chromatography coupled with multi-angle laser light scattering and refractive index detector (HPSEC-MALLS-RI) showed that 12 h was sufficient for complete digestion of polysaccharides from H. erinaceus. Laminaritriose (DP3) was used as an internal standard for quantification of all the oligosaccharides. The calibration curve for DP3 showed a good linear regression (R2 > 0.9988). The limit of detection (LOD) and limit of quantification (LOQ) values were 0.05 μg/mL and 0.2 μg/mL, respectively. The recovery for DP3 was 87.32 (±0.03)% in the three independent injections. To sum up, this proposed method is helpful for improving the quality control of polysaccharides from H. erinaceus as well as other materials.